ASIA TIMUR PUSAT PERTUMBUHAN BARU EKONOMI DUNIA - Abibullah Samsudin; Morshidi Sirat; Nooriah Yusof (Dewan Bahasa dan Pustaka, 2000)
Role of countries in South East Asia in economic growth and social development for its regions and the world.